Repoblación y gran propiedad en la región de los Montes de Granada durante el siglo XVI. El Cortijo - Luna Díaz, Juan Andrés (Chronica Nova. Revista de Historia Moderna de la Universidad de Granada)
This article focuses its attention on the farm cortijo) as a form of agricultural occupation and explotation used by the Castilians in the territory known by the name of Siete Villas. It is a socioeconomic model of open landscape, with a prevalence of peaceful countryside and scattered dwellings. The foundation was the land and its justification, ownership. The Castilian population established itself in this area in three different types of settlement which in many cases have endured into recent times: Villas (Montefrío, Illora, etc.), alquerías (Alomartes, Deifontes, etc.), and cortijos (Domingo Pérez, Campotéjar, etc.). The basic objective of these settlements was to supply the city of Granada with grain by cultivating new lands which had been granted as favours. The study of 120 cortijos through documents has led to the following conclusions: the most usual form of habitat is the isolated cortijo with 1 to 3 houses; there is ample correspondence between owner and cortijo; the largest properties belong to old Christians; the majority of the owners were inhabitants of Granada; and for the most part they possess the characteristics of what can be considered medium-sized property.